Resource allocation in MIMO-OFDM-based cooperative cognitive radio networks: optimal and suboptimal low complexity approaches - Adian, M. G.; Aghaeinia, H. (International journal of communication systems, 2016)
Summary The problem of resources allocation in multiple‐input multiple‐output‐orthogonal frequency division multiplexing based cooperative cognitive radio networks is considered, in this paper. The cooperation strategy between the secondary users is decode‐and‐forward (DF) strategy. In order to obtain an optimal subcarrier pairing, relay selection and power allocation in the system, the dual decomposition technique is recruited. The optimal resource allocation is realized under the individual power constraints in source and relays so that the sum rate is maximized while the interference induced to the primary system is kept below a pre‐specified interference temperature limit. Moreover, because of the high computational complexity of the optimal approach, a suboptimal algorithm is further proposed. The jointly allocation of the resources in suboptimal algorithm is carried out taking into account the channel qualities, the DF cooperation strategy, the interference induced to the primary system and the individual power budgets. The performance of the different approaches and the impact of the constraint values and deploying multiple antennas at users are discussed through the numerical simulation results. Copyright © 2014 John Wiley & Sons, Ltd. The problem of resources allocation in multiple‐input multiple‐output‐orthogonal frequency division multiplexing‐based cooperative cognitive radio networks with decode‐and‐forward strategy is considered in this paper. The optimal resource allocation is realized subject to transmit and interference power constraints, and because of high computational complexity of the optimal approach, a suboptimal algorithm is further proposed.